Targeting Procrastination Using Psychological Treatments: A Systematic Review and Meta-Analysis - Rozental, Alexander; Bennett, Sophie; Forsström, David; Ebert, David D.; Shafran, Roz; Andersson, Gerhard; Carlbring, Per (Frontiers in Psychology, 2018)
Background: Procrastination can be stressful and frustrating, but it seldom causes any major distress. However, for some people, it can become problematic, resulting in anxiety, lowered mood, physical complaints, and decreased well-being. Still, few studies have investigated the benefits of targeting procrastination. In addition, no attempt has previously been made to determine the overall efficacy of providing psychological treatments. Methods: A systematic review and meta-analysis was conducted by searching for eligible records in Scopus, Proquest, and Google Scholar. Only randomized controlled trials comparing psychological treatments for procrastination to an inactive comparator and assessing the outcomes by a self-report measure were included. A random effects model was used to determine the standardized mean difference Hedge’s g at post-treatment. Furthermore, test for heterogeneity was performed, fail-safe N was calculated, and the risk of bias was explored. The study was pre-registered at Prospero: CRD42017069981. Results: A total of 1639 records were identified, with twelve studies (21 comparisons, N = 718) being included in the quantitative synthesis. Overall effect size g when comparing treatment to control was 0.34, 95% Confidence Interval [0.11, 0.56], but revealing significant heterogeneity, Q(20) = 46.99, p < .00, and I2 = 61.14%, 95% CI [32.83, 84.24]. Conducting a subgroup analysis of three out of four studies using cognitive behavior therapy (CBT) found an effect size g of 0.55, 95% CI [0.32, 0.77], and no longer showing any heterogeneity, Q(4) = 3.92, p = 0.42, I2 = 0.00%, 95% CI [0.00, 91.02] (N = 236). Risk of publication bias, as assessed by the Egger’s test was not significant, z = -1.05, p = 0.30, fail-safe N was 370 studies, and there was some risk of bias as rated by two independent researchers. In terms of secondary outcomes, the self-report measures were too varied to present an aggregated estimate. Conclusions: Psychological treatments seem to have small benefits on procrastination, but the studies displayed significant between-study variation. Meanwhile, CBT was associated with a moderate benefit, but consisted of only three studies. Recommendations for future research are provided, including the use of more valid and reliable outcomes and a screening interview at intake.